Bioassay: Zebrafish as a new animal model in pharmacology - Khatib, Alfi (2020)
Zebraﬁsh (Danio rerio), a tropical freshwater ﬁsh and a popular aquarium ﬁsh belonging to the minnow family (Cyprinidae) of the order Cypriniformes. This species has been popular since the early 1970s as a valuable experimental model applied in studying vertebrate development, biological development and genetic illnesses. George Streisinger, a molecular biologist from the University of Oregon, was the first scientist to use zebrafish as a tool to study the nervous system. The zebrafish is an animal model that was established to be an ideal experimental model for several biological disorders. In this presentation, some application of zebrafish used as animal model in pharmacology are discussed including diabates, obesity, and cancer.